The effects of intermittent fasting for patients with multiple sclerosis (MS): a systematic review - Lin, Xiaoxiao; Wang, Shuai; Gao, Yue (Frontiers in Nutrition, 2024)
Some studies have investigated the impact of intermittent fasting (IF) for patients with multiple sclerosis (MS). We aimed to conduct a comprehensive systematic review to analyze and summarize all clinical studies concerning the effects of IF on patients with MS. We conducted an exhaustive review of information available in the Embase, Cochrane, and PubMed databases up until September 1, 2023. All clinical research relating to the impacts of IF for patients with MS were included. In total, this systematic review encompassed 5 studies, which included four RCTs and one pilot study. Each study involved was assessed of high quality. The results from these studies demonstrate that IF protocols could potentially serve as an effective dietary strategy for managing symptoms and improving the quality of life in individuals afflicted with MS. In conclusion, IF might be a potential beneficial dietary intervention for MS.However, the number of trials in this field is relatively limited. The largescale clinical trials to investigate the effects of IF for MS are urgently needed, which may be helpful to manage this intricate neuroimmune disorder.